A discourse analysis of english answers used in shangri-la dialogue. - Nguyễn,Thị Nhớ; Ngũ Thiện Hùng (ĐHĐN : ĐHĐN., 2015)
This study attempts to find out the discourse features of English Answers delivered by representatives or officials during Shangri-la Dialogue. Dwelling on one hundred samples in Shangri-la Dialogue collected from the Internet for recent years from 2006 to 2014, the study focuses on finding out some typical features in terms of the move types of English answers, lexical choice, cohesive devices and stylistic devices to suggest some implications for teaching English to Vietnamese learners, especially students in the press and diplomatic fields. The research was conducted based on the combination of a variety of methods, namely qualitative, quantitative and descriptive. The findings obtained show that the move types of English answers include Opening move, Answering move and Ending move. Regarding lexical choice, some popular Adverbs and Intensifiers were found as important words to attract the listeners and confirm the quality as well as the opinion mentioned in the English Answers. What’s more, cognition verbs and modal verbs were commonly used. With regard to cohesive devices, reference, conjunction and repetition are indispensable to create a smooth and cohesive discourse. For the stylistic devices, English Answers made use of repetition and parallelism with high frequency. It is hoped that the results of the research will serve as an access to a profound understanding of English Answers. Also, the study takes into consideration the application of answering strategy of English speakers. Furthermore, the study is expected to be recognized as a contribution to the practice of English teaching and learning, in particular, the improvement of speakers’ performance upon taking part in Asking and Answering Dialogue.
Master thesis in social sciences and humanities
Keywords: discourse analysis of english answers used in shangri-la dialogue; discourse analysis -- english answers used in shangri-la dialogue